2002
DOI: 10.4049/jimmunol.169.2.702
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Apoptotic Cells by Macrophages Induces Novel Signaling Events Leading to Cytokine-Independent Survival and Inhibition of Proliferation: Activation of Akt and Inhibition of Extracellular Signal-Regulated Kinases 1 and 2

Abstract: Recent evidence indicates that phagocytic clearance of apoptotic cells, initially thought to be a silent event, can modulate macrophage (Mφ) function. We show in this work that phagocytic uptake of apoptotic cells or bodies, in the absence of serum or soluble survival factors, inhibits apoptosis and maintains viability of primary cultures of murine peritoneal and bone marrow Mφ with a potency approaching that of serum-supplemented medium. Apoptotic uptake also profoundly inhibits the proliferation of bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
122
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 46 publications
5
122
0
1
Order By: Relevance
“…Wnt-3a and Wnt-10b represent canonical Wnt family members with well-established strong anabolic signaling in bone. Interestingly, recent studies demonstrated that macrophage-derived Wnt proteins are essential for tissue regeneration in kidney (30,31) and liver (32). In particular, phagocytosis of apoptotic debris was found to stimulate macrophage production of Wnt-3a, which mediated hepatocyte regeneration (32).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt-3a and Wnt-10b represent canonical Wnt family members with well-established strong anabolic signaling in bone. Interestingly, recent studies demonstrated that macrophage-derived Wnt proteins are essential for tissue regeneration in kidney (30,31) and liver (32). In particular, phagocytosis of apoptotic debris was found to stimulate macrophage production of Wnt-3a, which mediated hepatocyte regeneration (32).…”
Section: Discussionmentioning
confidence: 99%
“…We found that CR3 ligation inhibited LPS-induced ERK1/2 phosphorylation (our unpublished data), and because ERK inhibition could only partially recapitulate CR3 effects (our unpublished data), we must hypothesize that other molecules are involved in CR3 signaling. Given that apoptotic cells affect other MAPK pathway molecules (45,46), future efforts will be directed toward studying these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the form of cell death is important. We have shown that the signaling events induced in responding cells by apoptotic versus necrotic targets are often diametrically opposed (3,5,17). The different responses to these two forms of cell death can serve as a "gauge" by which surrounding cells assess the overall severity of an environmental stress: sudden and catastrophic in the case of necrotic targets versus more gradual and potentially adaptable in the case of apoptotic targets.…”
mentioning
confidence: 99%
“…To date, study of these effects has been largely focused on professional phagocytes, like macrophages (m). 2 For example, we have shown that apoptotic targets inhibit apoptosis and maintain the viability of primary m cultures even in the absence of serum or other survival factors (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation